EFFECT OF SPILANTHES FILICAULIS LEAF EXTRACT ON THE SURVIVAL RATE OF NILE TILAPIA, OREOCHROMIS NILOTICUS - Morah, Frank N.I.; Udofia, Etobong U. (Acta Scientiae et Intellectus, 2024)
Spilanthes filicaulis is an annual weed and medicinal plant which has insecticidal activity. The present work is focused on its effect on the survival rate of the Nile tilapia, Oreochromis niloticus. Introduction of Spilanthes filicaulis leaf extract into the aquarium resulted in erratic swimming, loss of reflex, de-colorization and eventually death of the fishes. Mortality rate increased with increase in concentration of the plant extract.